Answer:
It’s been a while.... I was send somewhere bad....
How are you
It’s chris Steven cummmings
And I’m sorry so sorry
Answer:
Step-by-step explanation:
P = 4x(x - 3) + 4y(y - 3) + 8xy
= 4x² - 12x + 4y² - 12y + 8xy
= (4x² + 8xy + 4y²) - (12x + 12y)
= 4(x² + 2xy + y²) - 12(x + y)
= 4(x + y)² - 12(x + y)
x+y =2 ⇒ P = 4.2² - 12.2 = 16 - 24 = -8
Answer:
b
Step-by-step explanation:
I Think B is the right answer
Answer:
X= -4
Step-by-step explanation:
^ you have to isolate the radical than raise each side to the power of its index which gets you
x= -4
Since 3 divides 42, 3xy itself is the greatest common factor of 3xy and 42xy.
Answer: 3xy